40Ar/39Ar geochronology of the North China and Yangtze Cratons: New constraints on Mesozoic cooling and cratonic destruction under East Asia. Issue 4 (21st April 2014) - Wang, Fei; Wang, Qinchen; Lin, Wei; Wu, Lin; Shi, Wenbei; Feng, Huile; Zhu, Rixiang
Abstract: Lithospheric destruction of the North China Craton (NCC) is a prominent phenomenon during the Mesozoic, but the timing and process are still in dispute. Furthermore, whether the Yangtze Craton (YTC) was also destructed is controversial. Twenty samples collected from the NCC and YTC were subjected to high‐resolution 40 Ar/ 39 Ar geochronological and thermochronological studies. Average cooling rates of 450–150°C were estimated, showing that a rapid cooling event (~12°C/Ma) occurred on the NCC but not on the YTC during the Late Mesozoic. Crustal thickness can be roughly estimated by using pure conductive cooling showing that the crust of the NCC in the Jurassic was thicker than in the Cretaceous. Nonlinear cooling histories and cooling rates obtained by using multidomain diffusion theory show that the upper crusts of NCC and YTC had different cooling patterns during the Mesozoic. Combined with the sedimentation rates on the NCC, we argue that lithospheric thinning of the NCC began in the northern portion at ~140–135 Ma and peaked in the central and eastern portions at ~125–100 Ma, at a cooling rate of ~9.6°C/Ma. In contrast, the YTC cooled gently during 200–75 Ma at a rate of ~1.2°C/Ma, implying that the lithospheric thinning did not happen there during this time. Pure conductive cooling suggests that the crust of the YTC in the Late Triassic was thicker than the NCC in the Cretaceous; therefore, we argue that the lithospheric destruction in the YTC might have occurred after ~75 Ma. Key Points: 40 Ar/ 39 Ar geochronology and thermochronology carried out Strong contrast cooling patterns for the NCC and YTC are identified Implications for dynamic setting of the eastern Asian continent are discussed